El origen de la familia Rodriguez del Banato a través de la historia militar del siglo XVIII el ascendiente español - Barsi, Béla (Acta Hispanica, 2017)
The author – the descendant of the brothers Ödön (Barsi) and Endre Rodriguez who managed to be successful in the Hungarian cultural life and who were the descendants of the Rodriguez family from Banat – during a nonprofessional research of various decades reveals the Spanish ancestors of the family. During the research he used the oral tradition and the relatively few written documents, preserved objects. The military history of the 18th century played an important role in the research because this was the principal cause of the Spanish migration in Hungary. However, without reading the basic work of the historian Zoltán Fallenbüchl (Spaniards in Hungary in the 18th century) this research would not have managed its goal. Considering the fact that the study mentions the cantonment of the regiment of Alcaudate around 1717 and following this lead, the inspection online of the registers of Osijek was started. This was that brought the desired success with the statement of the Hungarian delegation of the Military Archive of Wien where a person called Antonio de Rodriguez is mentioned who was lieutenant, then captain and who before his death in the battlefield, established his family in Banat.